Sources and outcomes of marital conflict of couples with a blind spouse and their coping styles - Bautista, Ana Remedios L.; Solomon, Relyssa Julia T.
This study focuses on the sources of conflict, coping styles, and outcomes of conflict of the 13 blind/sighted married couples with marriage lasting for more than 5 years residing in a Gawad Kalinga Community. The data were gathered through conducting an interview and administering the Dyadic Coping Inventory to the respondents. It was found that the sources of conflict were consistent with the common sources of conflict among marital couples. However, one source, a constant organized arrangement of things inside the household, is unique to the sample due to the consideration given to the visual impairment of the spouse. The different ways that the partners communicate their stress as well as respond to their partners distress were discussed in detail. In addition, each of the Dyadic Coping styles the couples manifest during conflict was described; most couples utilized Supportive and Common Dyadic Coping styles, indicating healthy relationships and attitudes towards conflict. Ultimately, the outcomes of conflict show that the couples generally approach each other directly after the conflict and engage in positive activities in order to recover and reconnect to each other.